IN VITRO STUDIES ON ANTIOXIDANT AND ANTIDIABETIC ACTIVITY OF PLEUROTUS EOUS MUSHROOM IN METHANOL AND AQUEOUS EXTRACT - K, Shoba; S, Krishnakumari (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study evaluates the antioxidant and antidiabetic activity of the mushroom. Methods: Antioxidant activity was evaluated using hydroxyl radical, hydrogen peroxide, and antidiabetic activity using Î±-amylase and Î±-glucosidase. Result: The antioxidant IC50 for the mushroom extracts methanol and aqueous(Hydroxyl radical) was found to be 290,440Î¼g/ml (Hydrogen peroxide) 475,370 Î¼g/ml and antidiabetic(Î± Amylase) IC50 was found to be 460,500 Î¼g/ml and (Î± Glucosidase) 325,280 Î¼g/ml respectively. Conclusion: The result obtained in the in vitro methods suggests that Pleurotus eous mushroom can be administered for its antioxidant and antidiabetic activity